2015
DOI: 10.1002/mabi.201500244
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Acid‐based Poly(anhydride‐esters) as Antioxidant Biomaterials

Abstract: Poly(anhydride-esters) comprised of naturally occurring, non-toxic phenolic acids, namely syringic and vanillic acid, with antioxidant properties were prepared via solution polymerization methods. Polymer and polymer precursor physiochemical properties were characterized, including polymer molecular weight and thermal properties. In vitro release studies illustrated that polymer hydrolytic degradation was influenced by relative hydrophobicity and degree of methoxy substitution of the phenolic acids. Further, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…71 Polymer degradation studies under physiological conditions found bioactive release to be controlled by polymer hydrophobicity; greater hydrophobicity decreased release rate. Released bioactive maintained antioxidant activity, as evident by a DPPH radical scavenging assay (Figure 8).…”
Section: Backbone Attachmentmentioning
confidence: 99%
See 1 more Smart Citation
“…71 Polymer degradation studies under physiological conditions found bioactive release to be controlled by polymer hydrophobicity; greater hydrophobicity decreased release rate. Released bioactive maintained antioxidant activity, as evident by a DPPH radical scavenging assay (Figure 8).…”
Section: Backbone Attachmentmentioning
confidence: 99%
“…Two phenolic acids, syringic acid (SGA) and vanillic acid (VA), were integrated into a polymer backbone by first synthesizing diacid units and then subjecting them to solution polymerization. 71 Polymer degradation studies under physio-logical conditions found bioactive release to be controlled by polymer hydrophobicity; a greater hydrophobicity decreased the release rate. The released bioactive maintained its antioxidant activity, as evident by a DPPH radical scavenging assay (Fig.…”
Section: Antioxidantsmentioning
confidence: 99%
“…The former trend may be due to the shorter C−O bond relative to C−C bond, which reduces the polymer flexibility, whereas the latter is consistent with the literature. 40,41 KA polyesters had a lower M w , with the exception of 6e, when compared to KA poly(carbonate-ester) counterparts, with M w ranging from 9.0− 30.2 kDa. As expected, when comparing KA polyester and KA poly(carbonate-ester) T g values derived from the same monomer, in comparison the polyester had consistently lower T g values.…”
Section: ■ Materials and Methodsmentioning
confidence: 96%
“…Phenolic acids have been extensively studied because of their bioactive properties and disease prevention and control capacities . At first, many scientists used them to substitute for chemical antioxidants and antimicrobials in foods . Afterward, evidence suggested that phenolic acids possess potentially protective effects against diseases caused by oxidative damage.…”
Section: Introductionmentioning
confidence: 99%
“…19 At first, many scientists used them to substitute for chemical antioxidants and antimicrobials in foods. 20 Afterward, evidence suggested that phenolic acids possess potentially protective effects against diseases caused by oxidative damage. Recently, the effective inhibitory effect of phenolic acids on cancer invasion and metastasis has also been widely investigated.…”
Section: ■ Introductionmentioning
confidence: 99%